Novel approach for the treatment of canine elbow hygroma with extracorporeal shockwaves - Verhoeven, Anika; Huels, Nikolaus; Harms, Oliver (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
A hygroma is a fluid filled cavity, which appears due to repetitive traumata over bony prominences. For canine elbow hygroma there is no satisfactory treatment option available. Small hygromas should not be treated at all. Larger hygromas that restrict the dog in daily life, are infected, painful, or ulcerated should be treated surgically with drainage or total excision. Surgical treatment of hygromas results in long rehabilitation times and is associated with a high complication rate. Extracorporeal shockwave therapy (ESWT) is widely used in human and veterinary rehabilitation medicine since several years. Even the mechanisms of action are not fully understood it has a wide range of indications. ESWT provides anti-inflammatory effects, promotes microcirculation, and is used for pain relief. In this case series of 4 consecutive cases in 3 dogs we treated hygromas with extracorporeal shockwaves each for 3 to 6 times usually on a weekly basis. All hygromas regressed completely and no complications were noted. Overall ESWT seems to provide a safe, easy-to-use, as well as cost-effective alternative treatment option for canine elbow hygroma.
Keywords: ESWT; physical therapy; rehabilitation; non-surgical; dog; small animal